1984
DOI: 10.1039/c39840000272
|View full text |Cite
|
Sign up to set email alerts
|

An e.s.r. study of the diborane radical anion in solution

Abstract: The e.s.r. spectrum of B2H6'in fluid ethereal solution indicates that this radical anion has an ethane-like structure with a one-electron B-B o bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 0 publications
3
16
1
Order By: Relevance
“…[1]C À is close to the coupling constant reported for [II]C À (a( 11 B) = 5.9 G) [19] but significantly smaller than a( 11 B) in [H 3 B·BH 3 ]C À (10.9 G) [13] and [(MeO) 3 B·B(OMe) 3 ]C À (46.3 G). [16] From the large a( 11 B) coupling constant in [(MeO) 3 B·B(OMe) 3 ]C À it has been deduced that the odd electron largely resides in a s-bonding orbital with considerable s character.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…[1]C À is close to the coupling constant reported for [II]C À (a( 11 B) = 5.9 G) [19] but significantly smaller than a( 11 B) in [H 3 B·BH 3 ]C À (10.9 G) [13] and [(MeO) 3 B·B(OMe) 3 ]C À (46.3 G). [16] From the large a( 11 B) coupling constant in [(MeO) 3 B·B(OMe) 3 ]C À it has been deduced that the odd electron largely resides in a s-bonding orbital with considerable s character.…”
Section: Methodssupporting
confidence: 75%
“…[6][7][8][9][10][11][12][13][14][15][16] Specifically, radical anions of the type [R 3 B·BR 3 ]C À ([I]C À , Scheme 1; R = H, OMe) were detected. [13][14][15][16] Moreover, during electrochemical studies on the reduction of Ph 3 B, Mills and DuPont found indications of B·B adduct formation between [Ph 3 B]C À and unreduced Ph 3 B. [17,18] In an attempt to arrive at more stable B·B radical anions by providing a suitably preorganized scaffold, Gabbaï and Hoefelmeyer introduced a 1,8-napthalenediyl bridge between the two boron atoms ([II]C À , Scheme 1).…”
Section: In1916g N Lewis Proposed That a Covalent Bond Is Broughtmentioning
confidence: 98%
“…However, in all of these cases the oxygen is singly coordinated, XO versus XBH 3 , as opposed to dicoordinated XOX versus XBH 3 X, as discussed here. We might also want to recall the transient formation of (BH 3 ) 2À (analogous to O 2À ) accompanied by (B 2 H 6 ) 2À (analogous to O 2 2À ) in the reduction of B 2 H 6 (Godfroid et al, 1994), and the solution phase characterization of the radical anion (B 2 H 6 ) À (Marti & Roberts, 1984) analogous to O À 2 . Indeed BH 3 and B 2 H 6 additionally mimic atomic and diatomic oxygen.…”
Section: Concluding Remarks 41 Chemical Considerationsmentioning
confidence: 99%
“…N. Lewis proposed that a covalent bond is brought about by a pair of electrons shared between two atoms [1] and still today the electron pair is central to the chemists view on chemical bonding. [13][14][15][16] Moreover, during electrochemical studies on the reduction of Ph 3 B, Mills and DuPont found indications of B·B adduct formation between [Ph 3 B]C À and unreduced Ph 3 B. [3] Owing to their intrinsically high reactivity, however, most molecules containing one-electron bonds are highly elusive and, in striking contrast to the large body of theoretical knowledge accumulated on such systems in the past decades, the paucity of experimentally characterized examples is remarkable: [4] With two exceptions, [5] experimental evidence has only been gathered for highly sensitive substances by means of elaborate techniques, such as matrix isolation, g-irradiation, H-atom abstraction, or one-electron reduction at low temperatures.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Specifically, radical anions of the type [R 3 B·BR 3 ]C À ([I]C À , Scheme 1; R = H, OMe) were detected. Our contribution finally clarifies controversially discussed [9][10][11][12][13][14][15][16] fundamental aspects of chemical bonding, such as: How does the length of an E·E one-electron bond compare to that of a conventional E À E two-electron bond? [17,18] In an attempt to arrive at more stable B·B radical anions by providing a suitably preorganized scaffold, Gabbaï and Hoefelmeyer introduced a 1,8-napthalenediyl bridge between the two boron atoms ([II]C À , Scheme 1).…”
mentioning
confidence: 99%